Effect of Early Intervention on Developmental Domains and Parent–Child Interaction Among Children With Developmental Delay: A Randomized Controlled Study. - Gündoğmuş, Ezginur; Bumin, Gonca; Yalçın, Sıddika Songül (American Journal of Occupational Therapy)
Importance: The scope of early intervention (EI) programs, which mostly focus on motor skills, needs to be expanded. Objective: To examine the effects of an EI on developmental domains and parent–child interactions. Design: Randomized controlled study. Participants: Children ages 24–36 mo with developmental delay (DD; intervention group, n = 30; control group, n = 40). Setting: Pediatric occupational therapy unit of Hacettepe University. Intervention: The intervention group received an intervention that used the Goal Activity and Motor Enrichment (GAME) approach and a home program, whereas the control group received a home program only. Both groups received the same intervention dosage. Outcomes and Measures: Developmental domains were assessed using the Bayley Scales of Infant and Toddler Development Third Edition (Bayley III) and the Ages and Stages Questionnaires (ASQ). Sensory processing was assessed with the Infant/Toddler Sensory Profile 2 (ITSP–2), social–emotional development with the ASQ:Social–Emotional (ASQ:SE), and parent–child interaction with the Parenting Interactions with Children: Checklist of Observations Linked to Outcomes (PICCOLO™). A compliance checklist was used to determine compliance with the home program. Results: A significant between-groups difference was found on all Bayley III and PICCOLO subscales and on the Gross Motor, Fine Motor, Problem-Solving, and Social–Emotional domains of the ASQ and ASQ:SE in favor of the intervention group (p <.05). The intervention group showed more typification (normal sensory processing) in sensory quadrants and general processing. Both groups were 100% compliant with the home program. Conclusions and Relevance: The GAME-based intervention for children with DD, including sensory and cognitive activities, is effective in improving developmental domains and parent–child interactions. Plain-Language Summary: The scope of early intervention programs mostly focuses on motor skills and needs to be expanded to include the essential roles of children's sensory and cognitive abilities. This study provides important insights into early interventions by occupational therapists and the impact on children with developmental delay and parent–child interactions. We found that the Goal Activity and Motor Enrichment (GAME) intervention for children with developmental delay, which includes sensory and cognitive activities, is effective in improving developmental domains and parent–child interactions. This study provides important insights into early interventions by occupational therapists and the impact on children with developmental delay and parent-child interactions.